Kristen kirke i et pluralistisk samfund - Nikolajsen, Jeppe Bach (Dansk Teologisk Tidsskrift, 2016)
Due to significant cultural and religious changes in the Western world, a significant theological debate has recently taken place. As Western societies are becoming increasingly pluralistic, an increasing number of theologians debate the consequences of this for the Christian church and for Christian theology. Against this background, the article demonstrates the existence of a monolithic unity of church and society in Denmark, Norway and Sweden from the sixteenth century up until the early twentieth century. Next, the article presents some empirical and theological arguments for the need for a stronger articulation of the church as a distinct social entity within late-modern pluralistic Nordic societies. Finally, the article discusses the notion of the embodiment oft he church, suggesting that this idea should be central in a developmentof a Nordic folk church ecclesiology that points to the future.